Anatomical features of the vertebral artery for transbrachial direct cannulation of a guiding catheter to perform coil embolization of cerebral aneurysms in the posterior cerebral circulation. Issue 3 (June 2015) - Iwata, Tomonori; Mori, Takahisa; Miyazaki, Yuichi; Tanno, Yuhei; Kasakura, Shigen; Aoyagi, Yoshinori
Background: Transbrachial approach is an alternative technique for coil embolization of posterior circulation aneurysms. The purpose of our study was to investigate the anatomical features of the vertebral artery (VA) for transbrachial direct VA cannulation of a guiding catheter (GC) to perform coil embolization of posterior circulation aneurysms. Methods: Included in retrospective analysis were patients who underwent transbrachial coil embolization of cerebral aneurysms in the posterior cerebral circulation by direct VA cannulation of a GC from 2007 to 2013. Investigated were patient characteristics, preoperative sizes of aneurysms, aneurysms location, the angle formed by the target VA and the subclavian artery (AVS), and the VA diameter at the level of the fourth cervical vertebral body (VAD) in the side of the transbrachial access route. Results: Thirty-one patients with 32 aneurysms met our criteria. The locations of aneurysms were the VA ( n = 16), basilar artery (BA) tip ( n  = 10), BA trunk ( n  = 3), BA superior cerebellar artery ( n  = 1), BA anterior inferior cerebellar artery ( n  = 1), and VA posterior inferior cerebellar artery ( n  = 1). The right brachial artery was punctured in 27 cases with 28 aneurysms as transbrachial direct cannulation of a GC, and left was in 4 cases with 4 aneurysms. The average AVS, ranging from 45° to 95°, was 77°, and the average VAD, ranging from 3.18 to 4.45 mm, was 3.97 mm. Conclusion: For transbrachial direct cannulation of a GC, it seems required that the AVS is about 45° or more and the VAD is about 3.18 mm or more.